2006
DOI: 10.1002/ca.20348
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the human metatarsals and phalanges

Abstract: Mathematical relation between metatarsals and between phalanges in terms of their lengths and widths in themselves is considered to be significant with respect to its functional and aesthetic roles. The objective of this study is to conduct measurements for determining lengths and widths of metatarsals and phalanges on the foot radiographs and to determine possible mathematical correlations between metatarsals themselves and between phalanges themselves in terms of their lengths and widths. Anteroposterior rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…The plantarflexor moment arms (pfMA) measured in 21 adult males by Maganaris et al [1] were found to range between 4.7 and 6.1 cm. The lengths of the metatarsals and phalanges in adult males have been found to exhibit similar variation, with between-subject standard deviations that range from 8 to 17 per cent of their mean values [2]. While the influence of such structural variation in the human foot and ankle upon function has not received much attention, variation across species is known to correspond to differences in functional demands.…”
Section: Introductionmentioning
confidence: 99%
“…The plantarflexor moment arms (pfMA) measured in 21 adult males by Maganaris et al [1] were found to range between 4.7 and 6.1 cm. The lengths of the metatarsals and phalanges in adult males have been found to exhibit similar variation, with between-subject standard deviations that range from 8 to 17 per cent of their mean values [2]. While the influence of such structural variation in the human foot and ankle upon function has not received much attention, variation across species is known to correspond to differences in functional demands.…”
Section: Introductionmentioning
confidence: 99%
“…Dogan et al. () found evidence of fixed proportions between the length and width of metatarsals and phalanges in the foot. The most intensively studied region has been the human hand.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have taken their measurements directly from bone specimens using traditional tools such as callipers and rulers (Davis, ; Guintard and Lallemand, ; Nacambo et al., ), while others measured the lengths directly on the bones using standard field‐measurement procedures and an osteometric board (Mcfadden and Bracht, , ). Although the changes in the focus‐film and object‐film distances can lead to the magnification of the objects on the film (Curry et al., ; Walter and Davies, ), several studies have involved the use of radiographs to measure some human and animal bones (Aydinlioglu et al., ; Livshits et al., ; Watson et al., ; Davies and Watson, ; Anthenill et al., ; Dogan et al., ). Many authors photographed horses with skin markers to measure some equine joint angles and bone dimensions (Crevier‐Denoix et al., ; Anderson et al., ).…”
Section: Introductionmentioning
confidence: 99%